2013
DOI: 10.1063/1.4828457
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear intrinsic variables and state reconstruction in multiscale simulations

Abstract: Finding informative low-dimensional descriptions of high-dimensional simulation data (like the ones arising in molecular dynamics or kinetic Monte Carlo simulations of physical and chemical processes) is crucial to understanding physical phenomena, and can also dramatically assist in accelerating the simulations themselves. In this paper, we discuss and illustrate the use of nonlinear intrinsic variables (NIV) in the mining of high-dimensional multiscale simulation data. In particular, we focus on the way NIV … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 43 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…The idea has been, in principle, proposed in the past [31] in the context of navigating effective free energy surfaces, and its incorporation in our Diffusion Map-based approach here is worth pursuing.In this paper the initially collected data came from a detailed set of kinetic ordinary differential equations, and the effective model for the reduced variables was also assumed to be a set of ODEs in these variables. The approach, however, can also, in principle, be used when the data do not need to come from a large set of ODEs, but, for example, from multiscale Stochastic Simulation Algorithm descriptions of chemical kinetic schemes (for such a recent application, see [32]). Moreover, as demonstrated also in the presented combustion example, the method should be able to cope with manifolds, whose dimensions possibly vary across distinct regions of the phase-space (see [23]); how to consistently express and solve reduced systems across manifolds with disparate dimensions remains out of reach of the present method, requiring further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The idea has been, in principle, proposed in the past [31] in the context of navigating effective free energy surfaces, and its incorporation in our Diffusion Map-based approach here is worth pursuing.In this paper the initially collected data came from a detailed set of kinetic ordinary differential equations, and the effective model for the reduced variables was also assumed to be a set of ODEs in these variables. The approach, however, can also, in principle, be used when the data do not need to come from a large set of ODEs, but, for example, from multiscale Stochastic Simulation Algorithm descriptions of chemical kinetic schemes (for such a recent application, see [32]). Moreover, as demonstrated also in the presented combustion example, the method should be able to cope with manifolds, whose dimensions possibly vary across distinct regions of the phase-space (see [23]); how to consistently express and solve reduced systems across manifolds with disparate dimensions remains out of reach of the present method, requiring further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that (invertible) functions of our measurements give rise to homeomorphic (and possibly isometric) embeddings, thereby conveying the same prototypical behavior [in the spirit of Whitney and the even stronger Nash embedding theorems and more specifically, Takens embedding for dynamical systems (36)(37)(38)(39)]. This points toward the feasibility of "gaugeinvariant" data mining (22,24,(40)(41)(42) through algorithms that do not depend on the measurement modality.…”
Section: Summary and Discussionmentioning
confidence: 69%
“…Furthermore, images taken from different viewing directions can be analyzed, as the vector diffusion maps parametrization will organize the images according to the viewing angle . Another direction for future work is related to the joint analysis of data sets provided by different imaging approaches, such as merging live imaging data of tissue morphogenesis with snapshots of cell signaling and gene expression from fixed embryos (Rübel et al, 2010; Krzic et al, 2012;Dsilva et al, 2013;Ichikawa et al, 2014). It would also be interesting to explore the connections between our proposed approach and recently developed methods for the ordering and classification of face images (Kemelmacher-Shlizerman et al, 2011.…”
Section: Discussionmentioning
confidence: 99%